2019
DOI: 10.3389/fmicb.2019.01221
|View full text |Cite
|
Sign up to set email alerts
|

Sphingomonas sp. Cra20 Increases Plant Growth Rate and Alters Rhizosphere Microbial Community Structure of Arabidopsis thaliana Under Drought Stress

Abstract: The rhizosphere is colonized by a mass of microbes, including bacteria capable of promoting plant growth that carry out complex interactions. Here, by using a sterile experimental system, we demonstrate that Sphingomonas sp. Cra20 promotes the growth of Arabidopsis thaliana by driving developmental plasticity in the roots, thus stimulating the growth of lateral roots and root hairs. By investigating the growth dynamics of A. thaliana in soil … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
72
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 127 publications
(80 citation statements)
references
References 93 publications
7
72
0
1
Order By: Relevance
“…Cra20 positively affects the growth of Arabidopsis thaliana (L.) Heynh. and increases plant tolerance to drought stress [45]. Similarly, enhanced growth and improved chlorophyll contents were observed in Lycopersicon esculentum Mill.…”
Section: Discussionmentioning
confidence: 70%
“…Cra20 positively affects the growth of Arabidopsis thaliana (L.) Heynh. and increases plant tolerance to drought stress [45]. Similarly, enhanced growth and improved chlorophyll contents were observed in Lycopersicon esculentum Mill.…”
Section: Discussionmentioning
confidence: 70%
“…With respect to the family Sphingomonadaceae different strains of Sphingomonas spp. have shown a positive effect on plant growth promotion [80] even under heavy metal [81] and drought stress [82]. LeFSe analysis showed the genus Arthrobacter was present in both rhizosphere plant but significantly enriched in rhizosphere of B. scandens.…”
Section: Discussionmentioning
confidence: 99%
“…Sphingomonas are widely distributed in nature, having been isolated from plant root systems and other sources. Reports showed that Sphingomonas stimulates the growth plants through phytohormone production, nitrogen fixation and driving developmental plasticity in the roots (Yang et al, 2014;Luo et al, 2019). Additionally, Sphingomonas was also shown to alleviate salinity stress in plants (Khan et al, 2017).…”
Section: Discussionmentioning
confidence: 99%